Serological and Molecular Study of Dengue Viruses in Different Hospitals of Nepal - Gupta, GP; Shah, Y; Poudel, A; Pun, R; Pant, KP; Kshetri, R; Pandey, K; Pandey, BD (Nepal Journal of Medical Sciences, 2013)
Background: Dengue Virus (DV) is an emerging mosquito borne viral disease and important public health problem in low land of Terai region which is also expanding to hilly region. Methods: This study was designed to estimate sero-prevalence of dengue virus infection in the post monsoon period (Jun-Dec) of 2010 in Nepalese patients with fever visiting hospitals of Birganj, Damouli, Biratnagar and Dhading Besi. Serum samples were collected from 280 patients visiting hospitals with history of fever & clinically suspected dengue fever. The sero-prevalence of dengue virus specific IgM was determined by enzyme linked immunosorbent assay (ELISA) kit (SD, Korea) Results: The anti-dengue IgM positivity was found to be 8.2%. The positive dengue cases were higher in male (10.5%) as compared to female (6.5%). Among different age groups, the highest positive cases (11.5 %) were from age group below 15 years followed by above 50 years age group with 8.5%. Out of 4 hospitals, the highest positive cases were in Tanahu District Hospital, Damouli (23.8%) followed by Koshi Zonal Hospital, Biratnagar (12.5%). Age and gender were found to be independent predictors. The highest numbers of dengue positive cases were in occupation group business (13.3%) followed by agriculture (11.5%). Conclusion: The dengue positivity was estimated in acute patients from different hospitals of Nepal by enzyme immunoassay and reverse transcriptase polymerase chain reaction. Therefore, the serological marker can be used to diagnose the acute patients of dengue during outbreaks. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 20-25 DOI: http://dx.doi.org/10.3126/njms.v2i1.7646